ESRA19-0372 To compare the analgesic efficacy of bilateral quadratus lumborum and transversus abdominis plane block in patients undergoing laparoscopic tapp repair of inguinal hernia: an RCT. (30th August 2019) - Bhoi, D; Roy, A; Darlong, V; Mohan Kumar, V; Chhabra, A; Prasad, G; Parshad, R; Bhattacharjee Kumar, H
Abstract : Background and aims: Laparoscopic trans-abdominal -pre-peritoneal repair of hernia is amongst the most popular hernioplasty surgeries. Peritoneal incision and iatrogenic pneumoperitoneum cause pain in this approach. QL block has been found to provide visceral pain relief by spreading local anaesthetic to the thoracic paravertebral space. Current study hypothesized that, bilateral QL block by trans-muscular approach would provide better pain relief than TAP block. Methods: After getting IEC approval, 40 ASA 1/2 patients aged between 18–65 years scheduled for either unilateral or bilateral inguinal hernia repair were randomized to receive either QL or TAP block with 20 ml of 0.25% ropivacaine on each side. the total 24 hrs post-operative fentanyl consumption was compared between the group as the primary objective. Results: Dermatomal coverage in patients assessed by absence of both cold and touch sensation was significantly higher for QL at T8(9 vs 2 p=0.009) and T9(12 vs 5 p=0.04). There was significant reduction in total 24 hr fentanyl consumption (552±229.56 vs. 735.5±264 p=0.01) in the QL arm, with longer duration (5.91±1.78 vs. 4.70±1.49 p=0.016) and lesser PCA bad demands (12 vs 31 p=0.001). Total performance time for QL was significantly longer (12.8±3.2 min vs. 10.85±1.606 min, p=0.01). QOR-40 at 24 hours and 3 months follow up result were comparable and no patient among either group experienced chronic pain. Conclusions: QL block had better analgesic efficacy than TAP block in the immediate 24 hr period with higher dermatomal coverage, however, the same didn't extrapolate at 3 month follow up period.